Indexing : a nuts-and-bolts guide for technical writers - Ament, Kurt, 1960- (William Andrew Pub., 2001)
Indexing: A Practical Guide for Technical Writers is a nuts-and-bolts guide to indexing. It explains in plain language and by example exactly how to index any type of print or online publication quickly, easily, and effectively. The sequential indexing method presented in the book has been battle-tested in high pressure publishing organizations in a variety of high-tech industries over the space of a decade. Because it is based on real-world success, this indexing method is bulletproof. Users of this guide will succeed as an indexer. Unlike other books on the subject, this book is focused on readers, not the subject itself. The book speaks directly to highly practical and often anti-academic technical writers who demand usability, reusability, and reliability. It is geared to people with ""Keep It Simple, Stupid"" signs on their cubicle walls. Proven end-user documentation techniques are employed to present proven indexing methods to readers who themselves develop end-user documentation for a living. They have zero tolerance for academic white papers on indexing. So, the book delivers the hard facts